Between keeping your head down and trying to get noticed: Agency workers in French car assembly plants - Christina Purcell; Paul Brook; Rosemary Lucas (Management Revue, 2011)
Numerical flexibility is commonly promoted as a driver of employment growth. However, contingent work is frequently associated with 'bad jobs', particularly for those in low skilled occupations. Agency work is a common and growing form of contingent work and is often promoted as a tool for facilitating the labour market integration of young workers. In France, young agency workers make up a significant part of the labour force within car assembly plants. Studies have shown that these workers have harsher working conditions than permanent co-workers and are subject to a 'despotic' factory regime. However, the triangular relationship, which frames the agency contract, may give rise to a more complex outcome in which the aspiration for stable employment mediates the coercion of labour market vulnerability.
Keywords: J47; J50; J63; J71; J81; 650; agency work; factory regimes; auto sector; agency autoworkers; hegemonic despotism; unions; labour process; Burawoy